The meiotic defects of mutants in the Drosophila mps1 gene reveal a critical role of Mps1 in the segregation of achiasmate homologs. - Gilliland, W.D.; Wayson, S.M.; Hawley, R.S. (Current Biology, 2005)
The conserved kinase Mps1 is necessary for the proper functioning of the mitotic and meiotic spindle checkpoints (MSCs), which monitor the integrity of the spindle apparatus and prevent cells from progressing into anaphase until chromosomes are properly aligned on the metaphase plate. In Drosophila melanogaster, a null allele of the gene encoding Mps1 was recently shown to be required for the proper functioning of the MSC, but it did not appear to exhibit a defect in female meiosis. We demonstrate here that the meiotic mutant ald1 is a hypomorphic allele of the mps1 gene. Both ald1 and a P-insertion allele of mps1 exhibit defects in female meiotic chromosome segregation. The observed segregational defects are substantially more severe for pairs of achiasmate homologs, which are normally segregated by the achiasmate (or distributive) segregation system, than they are for chiasmate bivalents. Furthermore, cytological analysis of ald1 mutant oocytes reveals both a failure in the coorientation of achiasmate homologs at metaphase I and a defect in the maintenance of the chiasmate homolog associations that are normally observed at metaphase I. We conclude that Mps1 plays an important role in Drosophila female meiosis by regulating processes that are especially critical for ensuring the proper segregation of nonexchange chromosomes.